Modeling the feasibility of fermentation-produced protein at a globally relevant scale - Fletcher, Andrew J.; Smith, Nick W.; Hill, Jeremy P.; McNabb, Warren C. (Frontiers in Sustainable Food Systems, 2024)
Fermentation-produced protein (FPP) is gaining global interest as a means of protein production with potentially lower cost and environmental footprint than conventionally-produced animalsourced proteins. However, estimates on the potential performance of FPP vary substantially, limiting assessment of its scalability and utility. We integrate life cycle analysis data with nutritional and economic data in an interactive online tool, simulating the requirements and consequences of fermentation at a globally-relevant scale. The tool demonstrates that production of an additional 18 million tonnes of protein annually via fermentation (~10% of 2020 global consumption) would necessitate 10-25 million hectares of feedstock cropland expansion/reallocation, utilise up to 1% of global electricity generation, produce 159 million tonnes CO2 equivalents, and have a total process input cost of 53.77 billion USD, with a negligible impact on nutrient supply beyond protein. This tool should be used to inform the debate on the future use of fermentation in the food system.